Human Resource Management in Improving The Quality of Education - Darul Qutni; Muhammad Kristiawan; Yessi Fitriani (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
this study aims to determine human resource management in improving the quality of education. The formulation of the problems in this research are: (1) how is human resource management in improving the quality of education?, (2) what are the obstacles faced in the implementation of human resource management in improving quality?, (3) what are the factors in the implementation of human resource management in improving the quality of education?, (4) how is the quality of education?. This research is a qualitative research with a qualitative descriptive approach. The data obtained were collected through observation, interview and documentation techniques. The results showed that human resource management at SD Negeri 170 Ogan Komering Ulu (OKU), both in quality improvement, implementation, supporting factors and the quality of education had been running optimally